Why GM matters inside the race to transform an American icon - Holstein, William J. (New York Walker, 2009)
Holstein goes deep inside GM on three continents to show what's really happening within one of the country's most iconic corporations. Demonstrates how GM has already radically retooled its entire operation, from manufacturing and cost structure to design.
Pt. I. The stakes -- 1. What went wrong -- 2. People on the front line -- 3. Does GM matter? -- 4. Who is Rick Wagoner? -- 5. 2005 : the crisis begins -- Pt. II. The GM transformation effort -- 6. Mastering the Toyota way -- 7. Going to Kansas City : making GMS work -- 8. Design rides again -- 9. Battling for the new Camaro's soul -- 10. The Chevy Volt -- 11. OnStar : "pretty good for an ex-locomotive salesman" -- 12. China : where Buick is king -- 13. The global GM -- Pt. III. The future -- 14. The battle of perception -- 15. Toyota : "human after all" -- Conclusion. The economic crisis and GM's future.
Includes index.
Keywords: General Motors Corporation; Automobile industry and trade -- United States